Dinâmica do potássio no solo e nutrição potássica da soja - Rosolem, Ciro Antonio [UNESP]; Bessa, A. M.; Pereira, HFM (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1993)
Potassium deficiency in soybeans has spread iii São Paulo State, Brazil, as a consequence of soil K reserve depletion. Exchangeable and nonexchangeable K dynamics in soil were investigated in order to understand the reserve exaustion and its significance to soybean nutrition. Soybean was grown in 8 1 pots with five soils differing in K and clay contents, in presence or absence of K fertilization. Soil samples were taken at 20 days interval and soybean was harvest at R6. Exchangeable (H2SO4 0,05 N) and nonexchangeable K (boiling HNO3) were estimated in soil sample. Two of the soils were very poor in exchangeable K, and even so there was no response in dry matter due to K fertilization. In spite of some differences in K contents in some of the soybeans parts, generally K absorption was not affected by K fertilization, except in grains. Potassium acumulation in soybean plants were affected by soils, but the response was not closely related to exchangeable K in soil. The main K source to the plants was the HNO3 extrated K, showing that this form is not at all nonexchangeable. After the period of maximum plant demand there was a sharp increase in extractable K in soil showing a tendency to a natural equilibrium.

A deficiência de K em soja tem-se tornado frequente no Estado de São Paulo, em decorrência do progressivo esgotamento em K dos solos. No presente trabalho, a dinâmica das formas trocáveis e não-trocáveis de K foi estudada para explicar os processos que levam ao esgotamento do solo, e a participação de formas não-trocáveis na nutrição da soja. Um experimento foi conduzido em vasos com cinco solos, na presença e ausência de adubação potássica. A soja foi colhida em R6, e amostras de solo foram tomadas a intervalos de 20 dias, analisando-se o K trocável (H2SO4 0,05 N) e não-trocável (HNO3 a quente). Dois solos apresentaram teores baixos de K trocável, e mesmo assim não foram observadas respostas em produção de matéria seca da soja. Apesar de se observarem algumas diferenças de teores de K em algumas partes das plantas, de maneira geral a adubação potássica influiu apenas no acúmulo de K nos grãos. Os teores de K trocável inicial não tiveram influência na absorção de K. A principal fonte de K para a planta foi o K extraído com HNO3 a quente, que se mostrou disponível, o que levanta dúvidas quanto a sua conceituação como não-trocável. Após o período de máxima demanda da planta o solo tendeu a um equilíbrio natural entre as formas de K.
Potassium dynamics in soil and soybean potassic nutrition
Keywords: NONEXCHANGEABLE-K; EXCHANGEABLE-K; K-ABSORPTION